Friends and Foes at Work: Assigning Teams in a Social Network - Thomas Daske (Technische Universität München, 2017)
In many firms, production requires the division of staff into teams. If only team performance is observable, moral hazard in teams is inevitable. This variant of moral hazard can be overcome or exacerbated by the interpersonal relationships among team members. I investigate how the division of staff into teams should account for the agents' social network of interpersonal relationships. Considering piece rate compensation for teams, I identify rules for efficient team assignment. Depending on the shape of individual effort costs, team assignment follows either a maximin or maximax rule with regard to team members' willingness to cooperate. Generally, the preferences of staff for team composition can collide with efficient production. A universal mechanism guaranteeing efficiency while delegating responsibility for team assignment to the agents does not exist. Successful staffing thus requires knowledge of the interpersonal relationships at work and, at times, control instead of delegation.
Additional information: This working paper/preprint is based on chapter II of my dissertation entitled "The Impact of Other-Regarding Preferences on Moral Hazard and Adverse Selection", which has been published under https://mediatum.ub.tum.de/?id=1356815 .
Keywords: D74; D82; D85; M54; 330; staffing; social preferences; social network; delegation; control